Extent of Response to Anti-Money Laundering and Terrorist Financing Instructions in Operating Banks in Jordan - Masadeh, Walid; Al Hassan, Abdullah (Jordan Journal of Business Administration, 2016)
This study aims to identify the extent of response of operating banks in Jordan to anti-money laundering and terrorist financing instructions issued by the Central Bank of Jordan. It also aims to measure the effectiveness of these regulations, the level of cooperation with the relevant government agencies and the impact of surrounding political and security circumstances on anti-money laundering and financing terrorism. To achieve the objectives of this study and to test its hypotheses, the descriptive analytical method was followed based on related data of the Central Bank instructions and the procedures employed by operating banks to fight money laundering and financing terrorism. A questionnaire was designed and distributed to the managers and staff of anti-money laundering departments in operating banks in Jordan, who were involved directly in complying with the instructions pertaining to anti-money laundering and terrorist financing issued by the Central Bank of Jordan. The sample consisted of 25 operating banks in Jordan until 2015 as ranked by the Central Bank of Jordan. 157 questionnaires were distributed and recovered, meaning a 100% response rate, which is equal to the number of managers and employees of the compliance departments in banks operating in Jordan. Many results were obtained, the most important of which are the high response by operating banks in Jordan to the instructions of anti-money laundering and terrorist financing issued by the Central Bank of Jordan, as well as the high level of implementing the instructions of fighting money laundering and terrorist financing in the banks operating in Jordan. In addition, the results revealed that there is an effective cooperation between the competent governmental authorities and the operating banks in Jordan in the fight against money laundering and terrorist financing. In light of these findings, the study introduces a number of recommendations, the most important of which is working to strengthen the cooperation level among the related parties in order to reach a high level of cooperation in the field of fighting money laundering and financing terrorism.